The effects of organizational commitment, organizational culture, and work discipline on the performance of state civil apparatuses - Muhammad Tamrin; Hendra Gunawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Purpose This study was to analyze the effect of the independent variables, namely organizational commitment, organizational culture and work discipline and their implications on the performance of the state civil apparatus at the Public Works and Public Housing Service in Jeneponto Regency, South Sulawesi Province. The research method is descriptive quantitative usingpath analysiswith the instrument test used is validity test and reliability test. Data collection techniques used primary and secondary data with a Likert scale. The results show that ASN performance can be increased by organizational commitment through affective and normative commitment by increasing the sense of belonging and responsibility to the organization, while the other variable, namely organizational culture tends to affect the application of good rules and a conducive organizational climate, then the ASN performance variable it would be much better if the commitment to the organization in its implementation was carried out by complying with the discipline of time and discipline of responsibility in the organization.